2017
DOI: 10.9790/3008-1202026473
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Ficus Carica Leaves Extract and Ubiquinone in a Chronic Model of Lithium Induce Reproductive Toxicity in Rats: Hindrance of Oxidative Stress and Apoptotic Marker of Sperm Cell Degradation

Abstract: groups treated with 25 mg /kg body weight of Lithium carbonate, FE (200mg/kg b.w) and CoQ10 (20 mg/kg b.w) (FC+CoQ10+LC). The experiment lasted for 60 days. Revealed data showed that the LC induces significant (P>0.05) increase in serum ALT, AST level, testicular GSSG, NO,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The decrease in MDA levels and the increase in antioxidant enzyme activity in the extract treatment group in this study indicated that the extract contained antioxidant secondary metabolites. The results of this study are in accordance with those of Haredy et al [45] who documented that the activity of antioxidant enzymes in the seminiferous tubules was significantly increased by F. carica treatment. This is also supported by the results of Omar et al [46] that found that F. deltoidea efficacy is attributed to its high phenolic and flavonoid content.…”
Section: Resultssupporting
confidence: 93%
“…The decrease in MDA levels and the increase in antioxidant enzyme activity in the extract treatment group in this study indicated that the extract contained antioxidant secondary metabolites. The results of this study are in accordance with those of Haredy et al [45] who documented that the activity of antioxidant enzymes in the seminiferous tubules was significantly increased by F. carica treatment. This is also supported by the results of Omar et al [46] that found that F. deltoidea efficacy is attributed to its high phenolic and flavonoid content.…”
Section: Resultssupporting
confidence: 93%
“…F. carica increased the levels of FSH more than that of LH, DHT, and estrogen which is therefore responsible for the increase in fertility in parent males. The outcomes of the present study are in accordance with a previous study by Haredy et al [ 19 ], who reported a reduction in lithium carbonate-induced liver toxicity by F. carica and increased endogenous activity of antioxidant enzymes (CAT and SOD2) and semen quality, while there was a significant decrease in markers of oxidative stress in testes, i.e., NO, 8OHdG, MDA and GSSG. Thus, it may be concluded that increased gene expression tends to reduce oxidative stress and in turn increases overall reproductive activity.…”
Section: Discussionsupporting
confidence: 93%
“…Phytoestrogens are compounds found in plants that have a similar structure and function of estrogen (Price and Rhodes, 1997). Also, the improvement of SSCs` proliferation in the presence of FC leaf extract may be due to FC containing saponin that act as testosterone like action (Haredy et al, 2017). In addition to estrogen, Tajik et al (2012) reported the involvement of testosterone in SSCs enrichment in the culture.…”
Section: Discussionmentioning
confidence: 99%
“…Also, after administration of FC leaf extract, spermatogenic arrest was rarely seen in seminiferous tubule of testis exposed to formaldehyde. Based on a compilation by Haredy et al, FC ameliorated Lithium carbonate -induced reduction in reproductive performance of male rats through its antioxidant and antiapoptotic properties (Haredy et al, 2017). A recent study also reported the profertility effect of FC leaf extract on streptozotocin-induced diabetic male rats.…”
Section: Introductionmentioning
confidence: 98%